Development of Teaching Materials Assisted by Book Creator in IPAS Material Subject of the Human Respiratory System to Improve Learning Outcomes for Grade V Elementary School - R. Teti Rostikawati; Aditya Rachman; Anggi Nur Pramesti; Novia Anjani Safitri; Siti Utami (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: The lack of interesting and interactive teaching materials in IPAS learning in elementary schools leads to low motivation and learning outcomes of students. Teaching materials that are still dominated by textbooks have not been able to accommodate diverse learning styles.Aims: This study aims to develop interactive teaching materials supported by the Book Creator application to enhance the learning outcomes of fifth-grade students on the topic of the human respiratory systemMethods: This research employed the Research and Development (R&D) method utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data were collected through validation questionnaires, student response surveys, learning outcome tests, and interviews.Result: The developed teaching materials received a “Very Good” category from media, material, and language expert validators. Students' learning outcomes increased from 53.3% (pre-test) to 90% (post-test) after using teaching materials.Conclusion: Teaching materials assisted by Book Creator are feasible, practical, and effective in increasing students' understanding and learning motivation on the material of the human respiratory system.